2023
DOI: 10.1007/s40753-022-00202-y
|View full text |Cite
|
Sign up to set email alerts
|

Student Understanding of the Sign of Negative Definite Integrals in Mathematics and Physics

Abstract: In a study of student understanding of negative definite integrals at two institutions, we administered a written survey and follow-up clinical interviews at one institution and found that “backward integrals”, where the integral was taken from right to left on the x-axis, were the most difficult for students to interpret. We then conducted additional interviews focused on backward integrals at a second institution. Our analysis uses the concept image framework and a recent categorical framework for mathematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
0
1
0
4
Order By: Relevance
“…Tercermin pada indikator keterampilan memaknai luasan di bawah kurva yang masih menjadi tren kesulitan yang paling banyak dibandingkan kedua indikator keterampilan dasar lainnya. Temuan ini sejalan dengan penelitian Bajracharya yang menyatakan banyak siswa yang kesulitan memaknai luasan di bawah kurva yang seharusnya menjadi "shortcut" ketika menentukan jarak tempuh/perpindahan melalui grafik kecepatan-waktu 𝑣(𝑡) dan/atau menentukan kecepatan melalui grafik percepatan-waktu 𝑎(𝑡) (Bajracharya et al, 2023). Apalagi ketika siswa diminta mentransformasi grafik yang membutuhkan kombinasi keterampilan memaknai luasan di bawah kurva dengan keterampilan membaca grafik menjadikan hal tersebut sangat sulit dipecahkan siswa.…”
Section: Hasil Dan Pembahasanunclassified
See 3 more Smart Citations
“…Tercermin pada indikator keterampilan memaknai luasan di bawah kurva yang masih menjadi tren kesulitan yang paling banyak dibandingkan kedua indikator keterampilan dasar lainnya. Temuan ini sejalan dengan penelitian Bajracharya yang menyatakan banyak siswa yang kesulitan memaknai luasan di bawah kurva yang seharusnya menjadi "shortcut" ketika menentukan jarak tempuh/perpindahan melalui grafik kecepatan-waktu 𝑣(𝑡) dan/atau menentukan kecepatan melalui grafik percepatan-waktu 𝑎(𝑡) (Bajracharya et al, 2023). Apalagi ketika siswa diminta mentransformasi grafik yang membutuhkan kombinasi keterampilan memaknai luasan di bawah kurva dengan keterampilan membaca grafik menjadikan hal tersebut sangat sulit dipecahkan siswa.…”
Section: Hasil Dan Pembahasanunclassified
“…Artinya, nilai kecepatan pada interval waktu 4s sampai 5s lebih besar dibandingkan dengan interval waktu 0s sampai 2s. Penelitian sebelumnya juga mendapati bahwa pemaknaan curam/landainya kemiringan garis masih menjadi tren kesulitan bagi siswa sehingga perlu mendapat perhatian khusus bagi guru (Ayop & Ismail, 2019;Bajracharya et al, 2023;Susac et al, 2018).…”
Section: Indikator 4; Kombinasi Keterampilan Membaca Grafik Dengan Ke...unclassified
See 2 more Smart Citations
“…Maharaj (2014) found that students had difficulty applying rules for integration. In addition, several studies reveal that students also have difficulty using integral concepts in the course of calculus (Bajracharya & Thompson, 2014;Bezuidenhout & Olivier, 2000;Cui & Bennett, 2006). This shows that students' understanding of integral needs serious attention, especially for prospective teachers in order to ensure no mistakes when teaching the concept of integral later.…”
Section: Introductionmentioning
confidence: 99%